Comparison of Sleep Disorders among Nightshift guard men in Iran University Hospitals Using ESS and PSQI questionnairesin 2009 - F Rahimpour; S Mohammadi; MA Aghilinejad; MS Attarchi; M Malek; N Dehghan (طب کار)
Abstract Introduction:More than 8-12% of healthy people suffered from sleep disorders worldwide. This problem evaluated among guards in a little past studies. We aimed to assess this defect among hospital guards of Iran university of Medical Sciences. Materials: 74 guards filled out two different questionnaires aboutsleep quality, ESS and PSQI. Demographic data were obtained based on another self-designed questionnaire. Results:All data were analyzedand scores of the questionnaires were compared among guards of different wards. The urgencyguards of Rasul e Akram hospital reflected more disorders than the other groups. Marriage state wasaffected on final results, despite cigarette smoking and obesity had shown no significantly effects. Conclusion: Sleep hygiene may have a trouble situation among guards and modification of the sleep habit could improve the majority of the disorder. -